Pengaruh Pola Pikir Kewirausahaan, Pendidikan Kewirausahaan, Dan Motivasi Berwirausaha Terhadap Minat Berwirausaha (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Aulia, Selsa Reza Putri; Nurhajati, Nurhajati; Khalikussabir, Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the effect of entrepreneurial mindset, entrepreneurship education, and entrepreneurial motivation on entrepreneurial interest in students of the Faculty of Economics and Business, Islamic University of Malang. The sample used in this study was 87 active students from the Faculty of Economics and Business class of 2020 who had taken advanced entrepreneurship courses. The data analysis method used in the study was multiple linear regression analysis. Data testing used is simultaneous hypothesis testing (F) and partial hypothesis testing (t). The results showed that simultaneously the variables of Entrepreneurial Mindset, Entrepreneurship Education, and Entrepreneurial Motivation had a positive and significant effect on Entrepreneurial Interest and based on the results of partial testing, the Entrepreneurial Mindset variable had a positive and significant effect on Entrepreneurial Interest, the Entrepreneurship Education variable had a positive and significant effect on Entrepreneurial Interest, and Entrepreneurial Motivation had a positive and significant effect on Entrepreneurial Interest of Students of the Faculty of Economics and Business, Islamic University of Malang. Keywords: Entrepreneurial Mindset, Entrepreneurship Education, Entrepreneurial Motivation and Entrepreneurial Interest